The determinants of Islamic social reporting disclosure and its impact on the profitability of sharia banks - Sultan Mubarok Mubarok (Journal of Islamic Economics, Management, and Business (JIEMB), 2019)
Purpose - This study aims to determine of disclosure level of Islamic Social Reporting (ISR) and its impact on profitability at Sharia Commercial Bank in Indonesia.Method - This study uses Good Corporate Governance (GCG), which is proxied with self-assessment, number of commissioners, and number of Sharia Supervisory Board (DPS), financial is proxied with company size, company age, DER, Social Cost, BOPO, FDR, and NPF. Profitability is proxied with ROA and ROE. The sampling technique used a purposive sampling method. There are 12 Sharia Banks that meet the criteria of the study sample period 2013-2017.The result - The results showed that: first, GCG hurt ISR. Second, financial factors have a positive effect on ISR. Third, GCG negative affects profitability; the greater the number of commissioners and DPS will have an impact on the material costs of the Bank. Fourth, financial factors have a positive effect on profitability. Fifth, ISR hurts profitability. Sixth, ISR mediates the relationship between GCG and financial factors with profitability.Implication  - This study helps sharia banks to maintain Islamic Social Reporting as a tool to get stakeholders’ trustOriginality -  This study uses a corporate social responsibility report, which also presents the aspect of religiosity.